PDI Perjuangan Party's Strategy in Winning the 2024 North Sumatra Gubernatorial Election - Rukiman Daulay; Mardian Idris Harahap (al-Afkar, Journal For Islamic Studies, 2025)
In the 2024 elections in North Sumatra, PDI Perjuangan showed a significant performance. As one of the major parties, they obtained the most votes in several electoral districts. In carrying out its political strategy, PDI Perjuangan also faces various challenges, including community polarization, inter-party competition, and internal challenges in cadre consolidation. Therefore, it is important to take a closer look at how PDI Perjuangan prepares its political strategy for the 2024 North Sumatra regional elections. North Sumatra faces a number of complex social and economic challenges, including inter-regional economic disparities, high unemployment rates, and the social impact of the COVID-19 pandemic. These issues are of major concern to the public and may influence their preferences in choosing regional leaders. This study aims to determine the “PDI-P Party Strategy in Winning the North Sumatra Governor Election in 2024”. This research was conducted at the Indonesian Democratic Party of Struggle of Medan City which is located on Jl. Jamin Ginting No.86, Simpang Selayang, Medan Tuntungan District, Medan City, North Sumatra. The method in this study uses a qualitative method with a field research approach. The results of this study conclude that PDI Perjuangan faces the 2024 North Sumatra Pilgub with a more mature and experience-based strategy from the previous election. The party carries candidate pairs with strong visions and missions and coalitions with several other parties to expand support. In increasing electability, PDI Perjuangan utilizes various campaign methods, including face-to-face approaches, the active role of volunteers, and the use of social media to reach voters in all regions of North Sumatra.